The Sweet Spot of Legitimacy A Manager's Guide - Rosser, Christian; Pfaff, Conradin (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides an overview of legitimacy-related challenges at hybrid organizations and demonstrates legitimacy's importance for the strategic development of organizations. In a reader-friendly way, it addresses the question of how hybrid organizations can gain legitimacy from the perspectives of key stakeholders. To do so, the book examines legitimacy management in the context of two real-world hybrid organizations - the Swiss Institute for Translational and Entrepreneurial Medicine and the Swiss Center for Design and Health in Bern, Switzerland - from both theoretical and practical perspectives. It shows why the systematic combination of three types of legitimacy has the potential to optimize the level of legitimacy in emerging hybrids, contributing to their success. It also explains how organizational legitimacy can be operationalized using governance legitimacy, purpose-rational legitimacy, and value-rational legitimacy. This book equips managers and executives working at hybrid organizations with useful guidance and hands-on strategic tools to develop legitimacy management strategies. It also offers a source of inspiration for academic research and teaching in this field.
1. Setting the Scene -- Legitimacy as Condition for a Hybrid's Success -- 3. Methodological Considerations -- 4. The Journey of the Sitem-Insel and the SCDH -- 5. Legitimacy Building in the Cases of the Sitem-Insel and the SCDH -- 6. Conclusion.
Keywords: Strategic planning; Leadership; Industrial organization; Nonprofit organizations; Business ethics; Public administration; Business Strategy and Leadership; Organization; Non-Profit Organizations and Public Enterprises; Business Ethics; Public Management